2023
DOI: 10.1039/d3gc00613a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient dimerization of perfluoroolefin with strong nucleophilic ionic liquid catalysts by adjusting the interaction of anions and cations

Abstract: Ionic liquids, as an efficient nucleophilic catalyst, is used for the first time in the dimerization of perfluoroolefin, and further promotes the greening of fluorochemical reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
(54 reference statements)
3
5
0
Order By: Relevance
“…Notably, under the same conditions, the traditional KF/crown ether system showed lower activity and that the catalytic activity of ionic liquid with [C 4 Mpyrr] + , [C 4 DMAP] + , [C 4 DMEA] + , and [C 3 OHDMAP] + as cations was higher than that of [C 4 Mmim][SCN] ionic liquid catalysts reported in the literature. 18 The results also indicated that [C 4 Py][SCN] was consistent with literature reports, and this result was related to the active hydrogen at the 4-position of pyridine. 29…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Notably, under the same conditions, the traditional KF/crown ether system showed lower activity and that the catalytic activity of ionic liquid with [C 4 Mpyrr] + , [C 4 DMAP] + , [C 4 DMEA] + , and [C 3 OHDMAP] + as cations was higher than that of [C 4 Mmim][SCN] ionic liquid catalysts reported in the literature. 18 The results also indicated that [C 4 Py][SCN] was consistent with literature reports, and this result was related to the active hydrogen at the 4-position of pyridine. 29…”
Section: Resultssupporting
confidence: 90%
“…According to our previous experience, among the studies comparing the impact of various common anions on hexafluoropropylene dimerization reactions, it was established that the SCN − anion exhibits strong nucleophilic characteristics and delivers the most effective catalytic performance. 18 Consequently, the anions for the synthesized ionic liquids were standardized as SCN − . Firstly, the effects of different cationic head groups on the catalytic performance of hexafluoropropylene dimerization were investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We herein propose a strategy of capping Lewis-base-functionalized monodentate ligands on the metal centers during the de novo synthesis of MOFs, by which the adjacent metal sites turn coordinatively unsaturated and then generate FLPs with the incorporated Lewis basic molecules. Considering that ionic liquids (ILs) are high-efficiency Lewis basic molecular catalysts by virtue of their intrinsic nucleophilic anions (e.g., halide ions) and tailored acidity/basicity, 16,17 we have designed a kind of monocarboxyl functionalized ILs as monodentate ligands. Based on the bottom-to-up assembly strategy, ILs are distributed on the framework to ensure large specific surface areas, open porous channels, and good thermostability, and FLP nanospaces consisted of ILs and unsaturated metal sites are constructed (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%